2017
DOI: 10.3390/ma10010093
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Accuracy and Internal Fit of 3-D Printing Laser-Sintered Co-Cr Alloy Copings

Abstract: Abstract:Laser sintered technology has been introduced for clinical use and can be utilized more widely, accompanied by the digitalization of dentistry and the development of direct oral scanning devices. This study was performed with the aim of comparing the marginal accuracy and internal fit of Co-Cr alloy copings fabricated by casting, CAD/CAM (Computer-aided design/Computer-assisted manufacture) milled, and 3-D laser sintered techniques. A total of 36 Co-Cr alloy crown-copings were fabricated from an impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 54 publications
2
66
1
Order By: Relevance
“…In vitro evaluations have reported mean gap values between 11 and 129.2 μm for the marginal and 48 to 100.9 μm for the internal surfaces of metal‐ceramic crowns on implant abutments . Freire et al evaluated the marginal fit of CAD/CAM monolithic ceramic and metal‐ceramic crowns and reported that monolithic lithium disilicate ceramic demonstrated the best marginal fit (27.95 μm), and that there was no significant difference between metal‐ceramic (57.42, 19.28 μm) and monolithic zirconia (58.05 μm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro evaluations have reported mean gap values between 11 and 129.2 μm for the marginal and 48 to 100.9 μm for the internal surfaces of metal‐ceramic crowns on implant abutments . Freire et al evaluated the marginal fit of CAD/CAM monolithic ceramic and metal‐ceramic crowns and reported that monolithic lithium disilicate ceramic demonstrated the best marginal fit (27.95 μm), and that there was no significant difference between metal‐ceramic (57.42, 19.28 μm) and monolithic zirconia (58.05 μm).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the subtractive manufacturing processes, a CAD/CAM system is often used to produce metal copings from prefabricated metal blocks . The short laboratory procedure saves time, and is relatively cost effective in comparison to other fabrication methods . The disadvantages of this method include the need for process precision, the generation of waste products, and wear of the equipment …”
mentioning
confidence: 99%
“…Initial database searching resulted in 284 studies, 1 additional study was identified through manual hand search. After duplicates removal, excluded studies from title and abstract, and assessing full text studies for eligibility, 17 studies (1,2,4,8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were included in this systematic review. Table 1 shows a summary of the studies included in this systematic review.…”
Section: Study Searchmentioning
confidence: 99%
“…However, in recent years, new fabrication techniques, which are more efficient, began to be used instead of conventional ones. (1,2) Along with the CAD/CAM milling, a paradigm shift in the procedure for fabricating the metal coping has come into life with the introduction of 3D printing technology. 3D printing can be used for the fab rication of metal structures either indirectly by printing in burn-out resins or waxes for a lostwax process, or directly in metal alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The alloys Cobalt-chromium (Co-Cr) and Nickel-Chromium (Ni-Cr) are used extensively in dental medicine for removable partial dentures, porcelain-fused-tometal crowns, and metal frames and particularly because they are, as compared to gold, bio-compatible, have a remarkable strength, corrosive resistant, and relatively less costly [1].. However, along with the benefits, during the manufacturing process, metal alloy exposure, as well as inaccurate working conditions and protection of workers, exposure to metals is hazardous to worker health.…”
Section: Introductionmentioning
confidence: 99%